2008
DOI: 10.1363/3400608
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Limiting Behavior and Contraceptive Choice Among Men in Nepal

Abstract: DATA AND METHODSUsually, data on family planning and family formation are derived from women's responses to survey questionnaires. Since 1990, the DHS has been collecting nationally representative data from men on a range of reproductive health issues, including contraceptive use and fertility behavior. However, these data have received little attention compared with data collected from women, possibly because men are thought to give less reliable information, especially regarding their attitudes and behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 13 publications
(13 reference statements)
3
55
2
Order By: Relevance
“…These results are in line with other studies conducted in other countries (10,16,23,28). Men who do not want to have any more children are likely to choose permanent methods only after they have 2 living sons (29). In certain literature, it is indicated that younger men were more likely than older men to have knowledge of a family planning method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with other studies conducted in other countries (10,16,23,28). Men who do not want to have any more children are likely to choose permanent methods only after they have 2 living sons (29). In certain literature, it is indicated that younger men were more likely than older men to have knowledge of a family planning method.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is well established that the use of contraception has increased with education (10,11,16,23,(26)(27)(28)(29)(30) and that being exposed to education and counseling have a significant effect on the behavior of an individual. A lower general educational level had a remarkable effect on reproductive health knowledge of soldiers from the eastern region of Turkey (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies reviewed did not report this association; rather, they reported the current number of living children and the desire for more than five children to be associated with men's participation in FP. 3,7,11,15,18,19 While men's marital status, their partner's age, the current number of living children and the desire for 5 children and more determined their level of involvement in the bivariate analysis, these same factors were not determining when the other factors were taken into account in the multivariate analysis.…”
Section: Factors Associated With Male Involvementmentioning
confidence: 99%
“…The situation is not made any better by fear of side effects of female methods. To these inhibiting factors must be added poor access to family planning services, 7 men-unfriendly FP services, unwelcoming healthcare workers, preference for large family sizes, religious sanctions, lack of finances, and long waiting times at FP clinics. 6 The aim of this study is twofold: 1) to determine the risk factors associated with male involvement in the choice of Family Planning methods; and 2) to describe the perceived barriers to male involvement in family planning.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the opposition of females or wives to the use of condoms is also embedded in this study, as they would question the practices of the male partner or their fidelity in the relationship. Therefore policies that are geared towards male reproductive attitudes cannot cease with increased condom usage, as is evident in this study as well as others, 18,[30][31][32][33] because clearly the current reproductive health programs are not reaching all the men of Jamaica.…”
mentioning
confidence: 74%